Exploring The Factors Behind Students' Disinterest In Learning English - Ghina Athiyyaturrahmah; Abdurrofi' Daman Huri; Selamet Riadi Jaelani (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to find out the causes of students' lack of interest in learning English language at Daen Rahil Vocational High School with the total of participants being 30 students. Dane Rahil Vocational High School, Lenek Daya Village, Aikmel, East Lombok District, West Nusa Tenggara Province was the site of this study. The researcher used a qualitative descriptive design methodology taken by random sampling which included observation, interviews, and document collecting by asking 5 pre-planned questions during the interview. The findings revealed that student problems such as a lack of vocabularies, still stiff in speaking, environmental factors that still believe English is not needed in the future, a lack of peers to practice with, a lack of motivation and support from those around them who still speak in their mother tongue.